LEADER PROGRAMME AS THE SOURCES OF FINANCING LOCAL ACTION GROUP ACTIVITIES IN THE MAZOVIAN VOIVODESHIP - Parlińska, Agnieszka; Ignar, Marek (Acta Scientiarum Polonorum. Oeconomia, 2016)
The article is dedicated to the analysis financing Local Action Group activities of the Mazovian voivodship from the LEADER Programme. The analysis covers LAG support capabilities from sources of the LEADER programme in years 2007-2013. Authors' aim is to evaluate funds used from the LEADER programme by LAGs in Mazovian voivodship. In Mazovian voivodeship is 35 LAG which have at their disposal 337 million PLN. It can be noted that the Mazovian voivodeship is the leader with the biggest number of submitted applications and signed contacts.